An Analysis of Education within Batak Society - Sirait, Rajiman Andrianus; Windarti, Maria Titik; Sukarna, Timotius (Berumpun: International Journal of Social, Politics, and Humanities, 2023)
Education has a crucial role in fostering the quality of human resources and promoting community development within Batak society. The significance of a gendered approach to education in Batak society stems from cultural and traditional viewpoints that delineate distinct roles for men and women in the realms of education and employment. Nevertheless, there has been a notable shift in cultural perspectives towards gender roles in the realm of education, as seen by the growing presence of women in both educational pursuits and professional occupations. Alongside the gendered approach, the biblical worldview exerts a notable influence on education within Batak society. The biblical perspective offers a robust ethical framework for education and instills a comprehension of its inherent objectives. Hence, it is imperative for education in Batak society to incorporate the biblical worldview as a foundational framework for imparting crucial moral principles. This work utilizes a qualitative research methodology, employing case studies and historical comparisons. Julia Sarumpaet is a prominent individual who has been actively involved in advocating for the advancement of women's rights. The correspondence she has written exhibits a notable similarity to the letters authored by prominent figures in Indonesian history. In the cultural context of Batak Toba, individuals of both genders are accorded a position of high esteem. The identical sentiment is also expressed within the pages of the Bible. Hence, it is imperative for men and women to engage in collaborative efforts, as this aligns with their inherent nature. In the absence of male offspring within a family unit, there is no inherent need to perceive any sense of lacking.